Strategic management of municipal owned entities in the City of Johannesburg. - Mkoka, Ina Tulisiwe (My University, 2014)
Abstract Strategic Management is a concept that is not widely given focus mostly in local government. Local Government is at the cornerstone of ensuring quality services are provided to the citizens of South Africa. In order to ensure that there is satisfaction to the citizens and public value is created, new approaches and models on effective management within Local government has become a necessity. With the amount of challenges that face local government, and the growing need to improve the quality of life of the South African Citizens, municipalities are more required that they move towards a more strategic approach that seeks to enhance service delivery. Institutions develop vision statements such that they devise strategies that will help them to grow, towards their vision statements. Effective strategic management tools have become important for public institutions to improve delivery of services, and organisational performance at large The research investigated the extent of alignment between the City Of Johannesburg‟s,(CoJ‟s) vision statement of being” A world class African city” with its Municipal Owned Entities,(MOEs) Strategic plans. The guiding principles in any strategic management process, whether in the public or private sector, are about understanding what changes are needed, how to implement and manage these changes, and how to create a roadmap for sustaining improvements that lead to better performance.1 The research provided recommendation to local government‟s institution, to contribute in the improvement of processes that affect strategic management, such that organisational performance is also enhanced.
MM 2014
Keywords: Local government, Strategic planning.